Phylogenetics of four sections of genus Dendrobium sw. (Orchidaceae) in Peninsular Malaysia - Moudi, Maryam (2013)
A phylogenetic study of the four sections (Aporum, Crumenata, Strongyle, and Bolbidium) of the genus Dendrobium (family Orchidaceae) was conducted by using molecular markers. One of the three largest orchid genera in the family Orchidaceae is the genus Dendrobium with an estimated 1580 species worldwide. In Malaysia, there are more than 250 species of which 86 species are found in Peninsular Malaysia. This genus is distributed from South- East Asia, west to the Himalayas, east to Japan, and south to the Pacific Islands, New Zealand and Australia. Dendrobiums are one of the most popular orchids for their medicinal and commercial values. These plants favor the tropical regions with high annual rainfall and without a significant dry season for growth. Classifications based on morphological characters have not been able to clearly divide these four sections and neither do they support their monophyletic origins. Therefore, detailed analysis using molecular data is required to ascertain their status. In this study, 22 fresh samples of the Dendrobium species were collected and sixteen of them was identified to the species level, whereas the other six were not able to be identified due to the lack of flowering structures that can aid identification. To date, there is no study on the phylogenetic relationship among species of the four sections of the genus Dendrobium in Peninsular Malaysia. Therefore, morphological characters combined with molecular evidence were used to clarify their relationships either to lump them together into one section or to reduce them into two sections or to maintain them in their current sections. Morphological analyses were conducted on the species of the genus Dendrobium belonging to the four sections (Aporum, Crumenata, Strongyle and Bolbidium) and the other belonging to the three sections (Dendrobium, Callista and Latouria), which are closely related to them. Molecular studies were carried out for the species of the genus Dendrobium using two phylogenetic analysis methods, Neighbor Joining Method (NJ) as the Distance method and Maximum Parsimony (MP), Maximum Likelihood (ML) and Bayesian analysis (BI) as character-based method. Seven nucleotide sequence data sets from three distinct genomes, chloroplast DNA genes (rbcL, matK, and trnL-F), nuclear ribosomal DNA (ITS), and low copy nuclear gene (Xdh) were used to construct the cladograms. In addition, the nucleotide sequences of selected genetic markers for some species of the genus Dendrobium were also retrieved from the NCBI database to facilitate the analysis. The morphological analysis showed that sections Aporum, Crumenata, Strongyle and Bolbidium formed a monophyletic group compared to three other sections Dendrobium, Callista and Lautoria. The results demonstrated that sections Aporum, Crumenata, and Strongyle were close to one another and were grouped into one clade. Although section Bolbidium was close to them, it formed a different clade by itself. The three other sections included in the analysis formed a separated clade from these four sections. Molecular data showed similar results that supported the four sections forming a monophyletic group, but the relationships among the sections were different when compared to the morphological result. Through molecular study, phylogenetic trees for chloroplast markers, nuclear gene markers and a combination of these markers were constructed based on different phylogenetic analysis methods (MP, ML, BI) using different softwares (PAUP*4.0 B 10, Mr Bayes 3.1.1. and Mega 5). Individual and combined analysis of the five gene regions (rbcL, matK, trnL-F, nrITS and Xdh) supported the monophyletic status (Boot strap Replicate and Posterior Probability more than 90%) of four sections (Aporum, Crumenata, Strongyle and Bolbidium) compared to the other three sections (Dendrobium, Callista and Latouria). Most of the ML and BI trees were congruent, whereas the MP trees showed different results. The phylogenetic trees revealed differences among the four sections, but overall, the molecular analyses showed close relationships between sections Aporum and Stongyle, and sections Crumenata and Bolbidium. However, some analyses showed the closeness among three sections Aporum, Strongyle and Bolbidium or among sections Crumenata, Strongyle and Bolbidium. Nevertheless, it was observed that sections Aporum and Strongyle were grouped together in most of the trees. The combined results of two gene regions; Internal Transcribed Spacer (ITS) and low copy nuclear gene (Xdh) showed that the nuclear genes are more reliable markers for the phylogenetic study of Dendrobium compared to the chloroplast DNA with a low level of resolution among the sections. The results from the nuclear markers suggested that the four sections are probably best considered as one section instead of four. Based on the ICBN rules, the name Aporum has a priority to be used for this new classification.